Detection of bovine respiratory syncytial virus, Pasteurella multocida, and Mannheimia haemolytica by immunohistochemical method in naturally-infected cattle - Yaman, Turan; Büyükbayram, Hüseyin; Özyıldız, Zafer; Terzi, Funda; Uyar, Ahmet; Keleş, Ömer Faruk; Özsoy, Şule Yurdagül; Yener, Zabit (Walter de Gruyter GmbH, 2018)
Abstract Introduction: The aim of this study was to determine the predisposing effect of bovine respiratory syncytial virus (BRSV) on Pasteurella spp. infection in naturally-induced pneumonia in cattle by immunohistochemical labelling. Material and Methods: Lungs of cattle slaughtered in the slaughterhouse were examined macroscopically, and 100 pneumonic samples were taken. The samples were fixed in 10% neutral formalin and embedded in paraffin by routine methods. Sections 5 μm in thickness were cut. The streptavidin-peroxidase method (ABC) was used to stain the sections for immuno-histochemical examination. Results: BRSV antigens were found in the cytoplasm of epithelial cells of bronchi, bronchioles, and alveoles and within inflammatory cell debris and inflammatory exudate in bronchial lumens. Pasteurella spp. antigens were detected in the cytoplasm of the epithelial cells of bronchi and bronchioles, and in cells in the lumens of bronchi and bronchioles. Eleven cases were positive for only one pathogen (six for BRSV and five for Pasteurella spp.), while 35 cases were positive for 2 pathogens: BRSV plus P. multocida (n = 21) or M. haemolytica (n = 14). Conclusion: The presence of high levels of BRSV in dual infections indicates that BSRV may be the main pneumonia-inducing agent and an important predisposing factor for the formation of Pasteurella spp. infections in cattle naturally afflicted with pneumonia.
Keywords: m. haemolytica; Veterinary medicine; Immunohistochemistry; P. multocida; Bovine respiratory syncytial virus; p. multocida; cattle; bovine respiratory syncytial virus; immunohistochemistry; SF600-1100; Cattle; M. haemolytica; Research Article; 2. Zero hunger; 3. Good health